Brazilian Portuguese Version of the Diagnostic Criteria for Temporomandibular Disorders Axis II: Translation, Cross-Cultural Adaptation and Measurement Properties - da Antunes da Cunha, Taísi; Chaves, Thaís Cristina; Pereira Júnior, Francisco José; de Gonçalves, Daniela Aparecida de Godoi [UNESP]; Alstergren, Per; Biasotto-Gonzalez, Daniela Aparecida (Wiley, 2025)
Background: The Diagnostic Criteria for Temporomandibular Disorders (DC/TMD) is a biaxial tool for TMD assessment. To implement a translated version in the Brazilian context, standardised adaptation and validation are necessary. Objective (s): To translate, adapt and verify the measurement properties of the DC/TMD Axis II instruments Pain Drawing (PD), Graded Chronic Pain Scale (GCPS), Jaw Functional Limitation Scale (JFLS) and Oral Behaviours Checklist (OBC). Methods: The translation and cross-cultural adaptation processes of orofacial-related Axis II instruments followed the Guidelines for Establishing Cultural Equivalency. The validation research was carried out with 117 Brazilians with TMD, in two assessment days. Structural validity, internal consistency, test–retest reliability, measurement error, construct validity—hypothesis testing, and ceiling and floor effects were tested. Results: PD showed substantial reliability (Kappa 0.63), and GCPS, JFLS and OBC showed excellent reliability over time (intraclass correlation coefficient > 0.85). The internal consistency was adequate for all instruments (Cronbach's alpha > 0.77) except for the functional activities domain of OBC (Cronbach's alpha = 0.48). Construct validity was good for all instruments (75% hypotheses confirmed), except for the OBC total score. Regarding parameters of structural validity, GCPS showed Goodness of Fit Index = 0.98 for the solution with two domains. JFLS and OBC presented Goodness of Fit Index < 0.90 for the solutions with three and two domains, respectively. Conclusion: The Brazilian Portuguese version of DC/TMD Axis II can be used in Brazil, but more studies are necessary to find an adequate structure for JFLS and OBC in a Brazilian sample.
Keywords: Brazil; orofacial pain; patient reported outcome measures; temporomandibular joint disorders; translations; validity and reliability